The fallen : rebel - Douglas, Kristina (New York : Pocket Books, 2013)
As a seer, Martha's visions aren't always reliable, but lately, her erotic dreams are driving her mad, her forbidden lover a dark stranger whose name haunts her: Cain. She knows the Fallen are in danger when the rogue angel unexpectedly appears in tongues of flame and turns his beautiful, wicked eyes on her, sensing everything she most wants to keep hidden. For a millennium, Cain has sought revenge for the Fallen's betrayal, and now he has finally returned to destroy their safe, tidy world. Using Martha as an unwitting pawn seems easy enough until Cain finds himself falling in love with her, just when it may be too late to save her from a brutal fate of his own design.